Estimation of foliage moisture content using near infrared reflectance spectroscopy - Gillon, D; Dauriac, F; Deshayes, M; Valette, J C; Moro, C (Agricultural and Forest Meteorology, 2004)
This study explored the relationships between the initial moisture content of leaves and their spectral properties when dry. Foliage moisture content (FMC in % dry-weight (DW)) was measured in 864 samples of eight common Mediterranean tree and shrub species from two sites during the summers of 2001 and 2002. All samples were dried, ground and scanned using a near infrared reﬂectance spectrophotometer. There were close relationships between FMC and foliage absorbance in the 400–2500 nm spectral range. Calibrations involving search for predictive relationships between spectral data and FMC were performed using partial least squares (PLS) regression that took into account all the spectral information. Calibration on FMC in each species from each year was predictive when a sufﬁciently large range of FMC values were available (R 2 = 0.93–0.99, standard error of cross-validation (SECV) = 2–7%). Moreover, calibration on FMC in all species combined, for each year or for both years together, was also predictive (R 2 = 0.92–0.95, SECV = 7%). It was thus possible to estimate the initial moisture content of a fresh foliage sample from its spectral characteristics when dried, whatever the species. However, mean foliage spectral absorbance changed from 1 year to the other. Consequently, FMC in leaf samples from each year was not estimated with accuracy when using the calibration established on samples from the other year but was accurately estimated when using the calibration established on samples from both years together. These close relations between dried foliage spectral data and FMC meant that some biochemical properties of the leaves associated with the changes in leaf water status caused changes in spectral reﬂectance which was preserved in the dried samples.
Keywords: foliage moisture content; infrared spectroscopy; mediterranean species; statistical calibration

Exploring the relationships between reflectance and anatomical and biochemical properties in Quercus ilex leaves - Ourcival, J M; Joffre, R; Rambal, S (New Phytologist, 1999)
Leaf anatomical parameters such as leaf mass per area (LMA) and biochemical composition can be used as indicators of leaf photosynthetic capacity. The aims of this study are to evaluate the potential of reflectance spectroscopy of fresh leaves for assessing and predicting various parameters, anatomical (LMA and tissue thickness) and biochemical (nitrogen concentration). This paper describes results obtained with fresh leaves of holm oak (Quercus ilex), an evergreen oak that is widely distributed from mesic to xeric habitats in the Mediterranean. Fresh leaves (560) were collected over 3 yr at six different sites, from the top to the bottom of the canopy. The reflectance of each leaf was obtained within 1 h of sampling with an NIRSystems 6500 spectrophotometer over the range 400–2500 nm. LMA was determined for all samples; biochemical and anatomical measurements were conducted over representative subsample populations of 92 and 87 leaves, respectively. Stepwise regression calibrations and partial least squares (PLS) calibrations were developed and compared with different spectral regions and mathematical treatments. Calibration equations had high coefficients of determination (r2 ranging from 0.94 for nitrogen to 0.98 for LMA and tissue thickness). The PLS regressions gave better results than stepwise regressions for all parameters studied. Compared with regressions calculated on raw spectral data, calculations on second derivatives of spectra improved results in all cases. The use of scatter corrections also improved results. These results show that visible and near-infra red reflectance can be used for accurately predicting anatomical parameters and the nitrogen concentration of fresh holm oak leaves. The results support the suggestion that high spectral resolution imaging spectrometry can be a useful tool for assessing functional processes in forest ecosystems.
Keywords: Anatomy; infrared spectroscopy; Leaf mass per area; Quercus ilex; reflectance; Thickness